The Moderating Role of Personal Growth Initiatives in The Influence between Religiosity and Academic Resilience - Hapsari, Dania Prima; Jianusa, Sisilia; Sulaiman, Ahmad (Faculty of Psychology, UIN Sunan Gunung Djati, Bandung Indonesia, 2025)
Academic resilience refers to a student's capacity to endure and adapt effectively to academic stressors. Religiosity is known to enhance academic resilience, although its effects may vary depending on other personal factors such as Personal Growth Initiative (PGI)—the conscious and active effort to develop oneself psychologically. This study aimed to examine whether PGI moderates the relationship between religiosity and academic resilience among university students in Malang City. A quantitative approach was employed using moderation analysis through Hayes’ Process Macro version 5.0. Data were collected from 384 students selected via accidental sampling, using the ARS-30, the Muslim Subject Religiosity Scale, and the PGIS-II instruments. The results indicated that PGI significantly and positively moderated the relationship between religiosity and academic resilience (β = 0.067; p = 0.000). These findings suggest that fostering students’ personal growth initiatives can strengthen the positive influence of religiosity on academic resilience, highlighting the importance of psychological self-development programs in educational settings.